Costs and Healthcare Resource Utilization Associated with Posterior Capsule Opacification After Cataract Surgery with Five Different Intraocular Lenses: An Economic Analysis for Spain - Belda JI; Placeres J; Elvira JC; Puig X; Pérez-Vives C; Zou M; Sun S; Yu J; O'Boyle D (Clinical Ophthalmology, 2022)
José I Belda,1 Javier Placeres,1 Juan Carlos Elvira,2 Xavier Puig,3 Caridad Pérez-Vives,4 Ming Zou,5 Shaohui Sun,5 Jing Yu,5 Derek O’Boyle6 1Hospital Universitario de Torrevieja, Torrevieja, Alicante, Spain; 2Hospital Universitario del Vinalopó, Elche, Alicante, Spain; 3Alcon Healthcare, S.A, Barcelona, Spain; 4Alcon Management SA, Cointrin, Switzerland; 5IQVIA Real World Solutions, Basel, Switzerland; 6Alcon Laboratories Ireland Ltd., Cork, IrelandCorrespondence: Derek O’Boyle, Alcon Laboratories Ireland Ltd., Cork, Ireland, Email derek.oboyle@Alcon.comPurpose: To estimate the economic impact of neodymium-doped yttrium aluminum garnet (Nd:YAG) laser capsulotomy and its related complications for five different intraocular lenses (IOLs) from the payer and hospital perspectives in Spain.Materials and Methods: The three-year incidence rates of Nd:YAG laser capsulotomy after cataract surgery with five different single-piece acrylic monofocal IOLs (AcrySof IOLs, AJL LLASY60, IOL Tech Stabibag, Medicontur Bi-flex, Zeiss Asphina) for 8293 patients were derived from odds ratios of multivariate analysis adjusted for age, gender, and diabetic retinopathy. A cost-consequence model for a hypothetical cohort of 2000 eyes was then developed to quantify the potential impact of Nd:YAG capsulotomy in terms of costs and time for each of the included IOLs, from the payer and hospital perspectives.Results: The adjusted three-year Nd:YAG laser capsulotomy incidence was 5.0% (95% CI 3.9 to 6.1) for AcrySof and ranged from 26.0% to 44.0% for the other four IOLs. The average costs of Nd:YAG treatment and related complications were € 261.90 for payers and € 19.99 for hospitals. The average time needed for Nd:YAG treatment and related complications was 32.82 minutes. Model estimates based on 2000 hypothetical cataract surgeries showed that AcrySof IOLs could lead to cost savings between € 110,259.90 and € 205,591.50 for payers. For hospitals, time, and cost savings with AcrySof ranged from 230.29 hours and € 8415.79 compared to Zeiss Asphina to 429.40 hours and € 15,692.15 compared to AJL LLASY60 IOLs.Conclusion: Post cataract surgery, AcrySof IOLs were associated with a significantly lower incidence of Nd:YAG treatment and its subsequent complications compared to other IOLs. Our analysis shows that IOL choice is an important factor that can reduce the burden for patients, payers, and hospitals.Keywords: cost, resources, Nd:YAG capsulotomy, cataract, PCO, IOL